2017
DOI: 10.1590/1807-3107bor-2017.vol31.0065
|View full text |Cite
|
Sign up to set email alerts
|

Comparing depth-dependent curing radiant exposure and time of curing of regular and flow bulk-fill composites

Abstract: The effect of restoration depth on the curing time of a conventional and two bulk-fill composite resins by measuring microhardness and the respective radiosity of the bottom surface of the specimen was investigated. 1-, 3-and 5-mm thick washers were filled with Surefil SDR Flow-U (SDR), Tetric EvoCeram Bulk Fill-IVA (TEC) or Esthet-X HD-B1 (EHD), and cured with Bluephase ® G2 for 40s. Additional 1-mm washers were filled with SDR, TEC or EHD, placed above the light sensor of MARC ® , stacked with pre-cured 1-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
1
0
1
Order By: Relevance
“…Literature describes several methods to evaluate the depth of cure, 32,33 making it difficult to compare our results with other studies; however, our data still agreed with the reported literature. 20,32 The results of this study showed a statistically significant difference for group Low 16 J/cm 2 , when compared to other groups (Figure 1).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Literature describes several methods to evaluate the depth of cure, 32,33 making it difficult to compare our results with other studies; however, our data still agreed with the reported literature. 20,32 The results of this study showed a statistically significant difference for group Low 16 J/cm 2 , when compared to other groups (Figure 1).…”
Section: Discussionsupporting
confidence: 74%
“…11,15 However, this work verified that this value could be overestimated, and a radiant exposure of 8 J/cm 2 was sufficient to achieve adequate properties in terms of depth of cure. However, depth of cure is a material-dependent variable [32][33][34] suggesting that intrinsic factors, such as the resin color and translucency could affect the light scattering during the photoactivation time. 35,36 Irradiance and the duration of exposure a r e i mp or t a nt fac tor s i n r e si n comp o sit e polymerization.…”
Section: Discussionmentioning
confidence: 99%
“…No intuito de corrigir algumas desvantagens da técnica incremental foram desenvolvidas as resinas bulk fill, elas podem ser inseridas na cavidade em profundidades de 4 a 5 mm (Savadamoorthi et al, 2017). A apresentação destas resinas pode ser em pasta ou fluida, sendo essa última utilizada como base para uma resina bulk-fill pasta ou uma resina convencional, por não apresentar resistência ao desgaste (Savadamoorthi et al 2017;Rodrigues et al 2017;P et al 2020).…”
Section: Introductionunclassified